2021
DOI: 10.1177/1369433221993296
|View full text |Cite
|
Sign up to set email alerts
|

Seismic response characteristics of multi-story subway station through shaking table test

Abstract: A series of shaking table tests were carried out to investigate the seismic response characteristics of a multi-story subway station. Dynamic responses, including accelerations of the soils and the underground structure, layer drift, dynamic earth pressure, and lateral deformation of soils were recorded and analyzed. Several seismic characteristics of multi-story subway station structures are figured out. It is found that in addition to the racking deformation, the rotation vibration is observed for the multi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…Other studies have focused on the analysis of structural internal force (Chen and Liu, 2018, Lei and Yong, 2020, Miao et al, 2020, Wang et al, 2021, Xu et al, 2020). Tang et al, (2020) conducted a shaking table test and found that the components of the bottom layer of a deep underground subway station construction, particularly the middle column, experienced cumulative damage, and other studies reported similar results (Chen et al, 2020, 2021, Miao et al, 2020). Seismic damage to underground structures in soft soil sites may be greater than that in liquefied sand sites (Chen et al, 2020).…”
Section: Introductionmentioning
confidence: 70%
“…Other studies have focused on the analysis of structural internal force (Chen and Liu, 2018, Lei and Yong, 2020, Miao et al, 2020, Wang et al, 2021, Xu et al, 2020). Tang et al, (2020) conducted a shaking table test and found that the components of the bottom layer of a deep underground subway station construction, particularly the middle column, experienced cumulative damage, and other studies reported similar results (Chen et al, 2020, 2021, Miao et al, 2020). Seismic damage to underground structures in soft soil sites may be greater than that in liquefied sand sites (Chen et al, 2020).…”
Section: Introductionmentioning
confidence: 70%
“…Ma Chao et al [10] analyzed the influence of soil mechanic parameters on the seismic performance of underground structures using numerical simulation. Chen Zhiyi et al [11] conducted vibration table tests on multi-layer subway stations to study their seismic response, finding that in addition to horizontal shear deformation, rotational vibration also occurs in subway stations. Bao Xiaohua et al [12] conducted numerical simulation studies on the interaction of multiple underground structures and found that pile foundations and upper structures have a significant impact on column shear forces in station structures.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the inter-story displacement angle of the subway station structure using elastic sliding bearings was significantly larger than that of the structure using fixed connections. Chen et al [18] revealed the relationship between dynamic earth pressure, rotational vibration and lateral deformation, which provides a reference for earthquake-induced soil-substructure interaction and seismic response characterization of multi-story subway stations. Qiu et al [19] presented the structural dynamic response law of a large-span underground structure under seismic action, produced by numerical analysis of a three-dimensional large underground structure, and they discussed the effect of the structural span on the response, and analyzed the contribution of the structural inertial response and soil deformation to the dynamic response of the model of the soil-structure interaction system.…”
Section: Introductionmentioning
confidence: 99%